Clinical study on the treatment of primary trigeminal neuralgia by robot-assisted percutaneous balloon compression - fayan, Dong; Qi, Zhan; Qiang, Gu; Xueting, Gao; Bei, Zhou; Lang, Li; Yanchao, Liang; Xuefeng, Wang (Frontiers in Surgery, 2022)
Background: C-arm-guided percutaneous puncture balloon compression alone has risk factors of puncture failure, complications, and poor prognosis. Robot-assisted PBC can effectively increase the one-time puncture success rate and improve the safety of the procedure. However, evidence on the superiority of robot-assisted PBC over C-arm-guided PBC alone remains relatively limited. Methods Retrospective analysis The clinical data of 60 patients with trigeminal neuralgia aged 60 years or older in the Department of Neurosurgery of the Fourth Hospital of Harbin Medical University from January 2021 to October 2021. There were 29 males and 31 females, and the patients' ages ranged from 60 to 79 years, with an average of 71.63 ± 5.12 years. The success rate of first puncture, total operation time, number of "pear-shaped" balloons, number of C-arm X-ray scans, and immediate postoperative relief rate were recorded in both groups, and follow-up was performed to evaluate the postoperative results and complications. The overall evaluation of postoperative results and complications was performed. Results Intraoperative balloon compression was successfully completed in all 60 patients, and the first puncture success rate was higher in the robot-assisted group than in the simple C-arm group, with a significant difference between the two groups (P<0.001). In terms of intraoperative balloon morphology, the number of "pear-shaped" balloons was higher in the PBC than in the C-arm-only PBC group, with a significant difference between the two groups (P<0.005). The degree of immediate postoperative remission in the robotic group was 0 VAS score, which was not statistically significant in both groups (P>0.05). By the final follow-up, the mean VAS score of the robot-assisted group was lower than that of the simple C-arm group, and both were statistically significant (P<0.05); complications of masticatory muscle weakness or abnormal facial sensation occurred in both groups after surgery, but the number of cases in the robot-assisted group was less than that of the simple C-arm group. Conclusion Robot-assisted PBC is better than PBC with a C-arm X-ray machine in terms of first puncture success rate, number of intraoperative balloon "pear-shaped" cases, number of C-arm X-ray scans and short-term efficacy.